(untitled) (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2019)
The repertoire of images derived from the formation of morphogenetic processes has been widely investigated in any scientific and humanistic study sector: from the pioneering kinetic art experiences, programmed art and generative art of the 60s and 70s, to digital spatiality and digital utopian architecture projects or morphogenetic architecture, to the 90s or recent experience, you can have a look at these currents with a critical eye which is in part appropriately detached given the temporal distance that has come to develop. Kinetic Art, Programmed Art, Generative Art, de–formative Architecture, and other names1 to indicate the processes and application experiences in different fields but which are derived from a common intellectual matrix: to generate forms, shapes, images or spaces from automated IT processes that do not delineate as a deterministic figuration from the hands of the author but as interaction between the author himself or herself and a computational thinking declined in various ways.